An improved switched diode multilevel inverter topology with fewer on state switches - Kubendran, V.; Shuaib, Y. Mohamed (Frontiers in Energy Research, 2022)
A double capacitor double diode double switch (DCDDDS) multilevel inverter is proposed in this paper to generates positive voltage and connecting polarity changing circuit of H-bridge inverter that generates negative voltage. The desired level is achieved by connecting the jth number of basic units in series. To generate more stepped level with fewer switches various algorithms, such as Natural, Binary, Trinary, Quasi-Linear sequences, and two proposed algorithms are discussed to determine the magnitude of DC voltage sources. The proposed multilevel inverter eliminates the need to turn on more power switches for different levels which is the highlight of this topology. The proposed multilevel inverter is compared in terms of the switch count, number of ON state switches per level, driver circuits, and total standing voltage with the conventional switched diode multilevel inverters. Real-time results from the test bench of OPAL-RT and simulation have demonstrated to validate of the proposed inverter.